UMA PERSPECTIVA ETNOGRÁFICA SOBRE A PRODUÇÃO DE MATERIAIS DIDÁTICOS EM 3D PARA ALUNOS COM BAIXA VISÃO - Rimolo, Annelize Damasceno Silva (2020)
This thesis aims to analyze how the process of producing didactic material occurred for students with low vision in a municipal school as well as to propose a complementary technic through the production of teaching material in 3D. Regarding the methodolo